2022
DOI: 10.2169/internalmedicine.7971-21
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus Treatment for Post-COVID-19 Interstitial Lung Disease

Abstract: With expansion of the COVID-19 pandemic, reports of post-COVID-19 interstitial lung disease (ILD) have been emerging. However, there are few reports regarding treatment. Some reports indicate that corticosteroids are effective for post-COVID-19 ILD, but the use of long-term corticosteroid carries risks of side effects. We administered tacrolimus to an elderly patient with post-COVID-19 ILD who suffered a respiratory failure relapse during steroid tapering. The respiratory status improved with tacrolimus in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(13 reference statements)
0
4
0
1
Order By: Relevance
“… 13 Accordingly, in cell line, it has been shown that tacrolimus inhibits the immunophilin pathway which SARS‐Co‐V replication depends on. 14 One case of interstitial pneumonitis after COVID‐19 treated with tacrolimus has been reported, 15 and a randomized, phase 2 clinical trial evaluating the efficacy and safety of a combination therapy of methylprednisolone and tacrolimus for severe pneumonia secondary to COVID‐19 is currently underway. 13 Our patient responded partially to the corticosteroid therapy but experienced a relapse when the PSL dosage was reduced to <30 mg.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Accordingly, in cell line, it has been shown that tacrolimus inhibits the immunophilin pathway which SARS‐Co‐V replication depends on. 14 One case of interstitial pneumonitis after COVID‐19 treated with tacrolimus has been reported, 15 and a randomized, phase 2 clinical trial evaluating the efficacy and safety of a combination therapy of methylprednisolone and tacrolimus for severe pneumonia secondary to COVID‐19 is currently underway. 13 Our patient responded partially to the corticosteroid therapy but experienced a relapse when the PSL dosage was reduced to <30 mg.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, umifenovir is considered as one of the antiviral drugs that can effectively treat COVID-19 patients. Tacrolimus may be effective in the treatment of post-COVID-19 acute interstitial lung disease, but does not prevent the progression of pulmonary fibrosis ( Ohgushi et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The role of immunosuppression in persisting ILD remains unprecised. A case report reported no benefit of tacrolimus on a patient with post-COVID ILD [48].…”
Section: Treatment Optionsmentioning
confidence: 97%